2004
DOI: 10.4049/jimmunol.172.3.1744
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Influence of Hepatitis C Virus on the Phenotype of Antiviral CD8+ T Cells

Abstract: Recent studies using MHC class I tetramers have shown that CD8+ T cell responses against different persistent viruses vary considerably in magnitude and phenotype. At one extreme, hepatitis C virus (HCV)-specific CD8+ T cell responses in blood are generally weak and have a phenotype that is perforin low and CCR7 high (early memory). At the other, specific responses to CMV are strong, perforin high, and CCR7 low (mature or effector memory). To examine the potential mechanisms behind this diversity, we compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
92
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 32 publications
10
92
1
Order By: Relevance
“…It has been suggested that high viral levels are predictive of long-term outcome after OLT; in one series, HCV RNA level higher than 1 log mEq/mL at 3 months after OLT had a 70% sensitivity (but only 45% specificity) for predicting fibrosis score higher than 2 at 1 year. 29 Clearly, measurement of HCV RNA alone is not sufficiently robust or specific as a predictive marker and, as demonstrated in our study, patients with mild HCV recurrence may have extremely high circulating levels of HCV RNA (e.g., patients 19,20,22,23).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that high viral levels are predictive of long-term outcome after OLT; in one series, HCV RNA level higher than 1 log mEq/mL at 3 months after OLT had a 70% sensitivity (but only 45% specificity) for predicting fibrosis score higher than 2 at 1 year. 29 Clearly, measurement of HCV RNA alone is not sufficiently robust or specific as a predictive marker and, as demonstrated in our study, patients with mild HCV recurrence may have extremely high circulating levels of HCV RNA (e.g., patients 19,20,22,23).…”
Section: Discussionmentioning
confidence: 95%
“…8. Combined IFN-␥ ELISPOT results (SEM) in response to 5 recombinant HCV antigens demonstrate differences between patients (n ϭ 15) who subsequently developed mild recurrence (18)(19)(20)(21)(22)(23)(24) versus those who developed severe recurrence (10-17) (*P Ͻ .05 between mild and severe groups for specific antigen by two-tailed t test). There was no significant difference between viral levels (copies/mL) in severity groups at the different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Treg might be an important target in future therapies against cancer or chronic infectious diseases [24]. A functional impairment of CD8 + T cells has also been described in chronic viral infection effecting humans, like human immunodeficiency virus (HIV) and hepatitis C virus (HCV) [35][36][37][38][39][40][41]. In addition, in both HIV and HCV infection CD4 + Treg have been reported to suppress antiviral T cell responses [1,[42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to control HCV replication has also been associated with functional defects of virus-specific CD8 + cytotoxic T lymphocytes (CTL) [7][8][9][10] and, most recently, to the appearance of viral escape mutations in immunodominant CD8 + CTL epitopes associated with a lack of or relative defects in HCV-specific CD4 + T cell responses [11][12][13]. Adaptive immune defects during HCV infection are not limited to HCV-specific immune responses and may reflect the broader effects of HCV on the editing of T cell responses also on other antigen specificities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Failure to control HCV replication has also been associated with functional defects of virus-specific CD8 + cytotoxic T lymphocytes (CTL) [7][8][9][10] and, most recently, to the appearance of viral escape mutations in immunodominant CD8 + CTL epitopes associated with a lack of or relative defects in HCV-specific CD4 + T cell responses [11][12][13]. Adaptive immune defects during HCV infection are not limited to HCV-specific immune responses and may reflect the broader effects of HCV on the editing of T cell responses also on other antigen specificities [14].Perturbations of the innate immune system, including dendritic cell (DC) and natural killer (NK) cell function, are likely to contribute to the skewed finetuning of anti-HCV CD8 + and CD4 + T cell immune responses leading ultimately to T cell dysfunction [15,16]. Evidence supports an involvement of innate immune mechanisms in the editing of the adaptive immune response to intracellular pathogens or tumor cells.…”
mentioning
confidence: 99%